Strategies for Dealing with Public Problems and Pandemic and Contagious Diseases from Viewpoint of Qur’ān and Narratives - Sayyed Ziaoddin Olyanasab; Hussein Jala'i Hussein Jala'i Nobari (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2021)
The present study aimed to describe the Qur'ānic and narrative strategies for dealing with public problems and pandemic and contagious diseases. This descriptive-analytical study was done through library research and analyzing reliable Qur'ānic and hadith sources. The analysis of the hadith sources indicated that when public problems, particularly the pandemic and contagious diseases, occur, we are recommended to visit a physician, not to leave our homes and cities, and not to travel to the cities where the disease has spread. Moreover, we are advised to frequently, particularly during difficulties, pray to God Almighty. The findings of the study also showed that there was no inconsistency between the revelatory teachings, including Qur’ān Verses and narratives, and the reliable scientific findings regarding human health. However, the revelatory teachings have recommended us to constantly pray to God, and deemed it necessary.